2016
DOI: 10.1038/nn.4389
|View full text |Cite
|
Sign up to set email alerts
|

LTD-like molecular pathways in developmental synaptic pruning

Abstract: In long-term depression (LTD) at synapses in the adult brain, synaptic strength is reduced in an experience-dependent manner. LTD thus provides a cellular mechanism for information storage in some forms of learning. A similar activity-dependent reduction in synaptic strength also occurs in the developing brain and there provides an essential step in synaptic pruning and the postnatal development of neural circuits. Here we review evidence suggesting that LTD and synaptic pruning share components of their under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 148 publications
(202 reference statements)
4
72
0
Order By: Relevance
“…In the SCG of α3/4E-BP-DKO mice, there is less differential strengthening among inputs; nonetheless, synapse elimination of preganglionic axons occurs in the absence of synaptic transmission. Therefore, in sympathetic ganglia, a differential in synaptic strength does not determine which axons are retained and/or which are eliminated, challenging the notion that a differential in synaptic strength determines which synapses are stabilized and which are eliminated (Katz and Shatz, 1996; Piochon et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In the SCG of α3/4E-BP-DKO mice, there is less differential strengthening among inputs; nonetheless, synapse elimination of preganglionic axons occurs in the absence of synaptic transmission. Therefore, in sympathetic ganglia, a differential in synaptic strength does not determine which axons are retained and/or which are eliminated, challenging the notion that a differential in synaptic strength determines which synapses are stabilized and which are eliminated (Katz and Shatz, 1996; Piochon et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, we compared molecular signaling cascades involved in LTD and developmental synaptic pruning at synapses in the visual cortex, the cerebellum and at the neuromuscular junction, and found that at each type of synapse the signaling pathways used for developmental and adult plasticity almost completely overlap (Piochon et al, 2016a). This observation suggests that forms of synaptic plasticity found in the adult brain (LTD and LTP) may serve similar functions as their equivalents in the developing brain, namely the weakening / elimination of weak synapses and the strengthening / stabilization of efficient ones.…”
Section: Intrinsic Plasticity: Cellular Mechanisms and Relevance To Lmentioning
confidence: 99%
“…Here, we present a different perspective, which looks at the immediate cellular consequences of synaptic and intrinsic plasticity mechanisms, stripped down from any traditional assumptions about their respective roles in learning. In this view, LTP and LTD change synaptic weights in an experience-dependent manner, and provide the processes needed to establish proper synaptic connectivity between neurons, similar to the synapse stabilization and pruning events that shape neural circuits during development (Piochon et al, 2016a). It remains undisputed that LTP has the potential to contribute to information storage by enhancing the probability that activation of the potentiated synapse(s) contributes to spike firing in the postsynaptic neuron.…”
Section: The Synapse Versus the Neuron As The Critical Site In Memorymentioning
confidence: 99%
“…Importantly, deficient LTD, impaired motor learning, motor discoordination, and impaired climbing fiber synapse elimination are all restored by Purkinje cell-specific expression of mGluR1a, a predominant splice variant in Purkinje cells, into global mGluR1-knockout mice 28 . This result clearly indicates that the mGluR1 cascade within Purkinje cells is essential for neural circuit development, synaptic plasticity, and motor learning in the cerebellum 23, 40 .…”
Section: Introductionmentioning
confidence: 77%